2007
DOI: 10.1177/112067210701700114
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations in Fetal Alcohol Syndrome

Abstract: The most common ocular findings were anomalies of retinal fundus and minor changes in the outer region of the eyes. The authors noted better VA and less severity of disease than others, which might be due to a different selection of patients, different pattern of alcohol consumption, or genetic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 8 publications
(7 reference statements)
8
33
0
3
Order By: Relevance
“…A recent Portuguese study of 32 children with FAS and 25 controls reported retinal vessel tortuosity in 30% and optic nerve hypoplasia in 25% of the children with FAS, lower rates than reported from Sweden. 11 This group also noted that their patients had better visual acuity (82.7% with normal acuity vs 35% in the Swedish study), and that the malformations were notably less severe than those seen in the Swedish study. 13 The authors suggested that referral/selection bias, drinking patterns, and genetic factors may play significant roles in the varying rates and severity of abnormalities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent Portuguese study of 32 children with FAS and 25 controls reported retinal vessel tortuosity in 30% and optic nerve hypoplasia in 25% of the children with FAS, lower rates than reported from Sweden. 11 This group also noted that their patients had better visual acuity (82.7% with normal acuity vs 35% in the Swedish study), and that the malformations were notably less severe than those seen in the Swedish study. 13 The authors suggested that referral/selection bias, drinking patterns, and genetic factors may play significant roles in the varying rates and severity of abnormalities.…”
Section: Discussionmentioning
confidence: 92%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These disorders may include external eye malformations, intraocular abnormalities, and impaired visual acuity. 3,4,19 Previous investigations had limitations, including studying only children with FAS who were referred for ophthalmologic evaluation because of known or suspected problems, providing little or no information on the extent of in utero alcohol exposure, performing limited evaluations of visual function, and examining only a small number of subjects.…”
Section: Conclusion Previous Research Has Found That Children With Fmentioning
confidence: 99%
“…Our study confirmed the findings of previous studies with FAS children, which found that these patients have smaller optic discs than normal individuals of the same age. 7,8,10,11,17,18 Unlike the other FAS studies, our sample consists of a group of young adults with similar ages (16 -26 years), which increases the strength of our results, since we potentially reduced the more pronounced optic disc morphometric variation that occurs in childhood with aging.…”
Section: Discussionmentioning
confidence: 99%
“…External ocular signs include short horizontal palpebral fissure, epicanthus, hypertelorism, blepharoptosis, telecanthus, strabismus and nystagmus. [7][8][9][10] Intraocular signs most commonly include optic disc hypoplasia, tortuosity of retina vessels, microphthalmus and impaired vision and also cataract, other anterior segment abnormalities, and coloboma. [7][8][9][10] Alcohol-induced optic disc hypoplasia is a common feature in FAS, which is estimated to occur in up to 48% of FAS children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation